Seasonality in the occurrence of Guiana dolphin, Sotalia guianensis (Cetacea: Delphinidae) in Port of Malhado, Ilhéus, Bahia, Brazil (Research, Society and Development, 2022)
The seasonal occurrence of S. guianensis was analyzed in the port of Malhado, Ilhéus, Bahia, Brazil. The survey was conducted through an electronic theodolite, between December 2008 and November 2009, totaling 358.3 hours of sampling effort and 173.8 hours of effective sightings. The number of individuals, size and composition of the groups, time of arrival and departure of animals and the angles proceeding from theodolite reading were recorded. The stations were divided into summer (October to March) and winter (April to September) and periods of the day were categorized according to the angles of sunlight on the water surface. The angles from 0° to 45° was correspondent to the period between 08:00 and 14:00 and 10:00 h and 16:00 h and the angles from 45° to 90° from 10:00 to 14:00 h. The mean size of the groups (= 4.1 ± 1.98) did not vary seasonally (z = 2.063, p = 0.039), but the number of groups (34 in summer and 65 in winter), number of specimens (162 in summer and 384 in winter), the mean theodolite tracking time (=46.09 in the summer and =122.07 in the winter) and area occupation area (1.60 km² in the summer and 2.45 km²) were higher in winter. There was no significant variation in the number of individuals for periods of sunlight (z = 0.30, p= 0.38). It was observed that there is seasonal variation in the distribution of S. guianensis nearby port and this may be related to seasonal variation in prey abundance.